PENGARUH PAJAK HOTEL, PAJAK RESTAURAN, RETRIBUSI OBYEK WISATA, BEA PROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB), TERHADAP PENDAPATAN ASLI DAERAH - Sri Ayem; Seriani Hamrin (Universitas Muhammadiyah Makassar, 2021)
This study aims to determine the effect of hotel taxel, restaurant taxes, tourist attraction fees, land and building rights acquisition fees on local revenue in West Manggarai Regency. This type of research is quantitative research. The population in this study is the report of West Manggarai Regency Original Revenue and Tourist Object Retribution in 2016-2019. The sample of this study used the purposive sampling method. The data source used is secondary data. Hypothesis testing in this study using multiple linear regression analysis method with SPSS program. The results showed thad hotel tax had a positive but not significant effect on local revenue. Restaurant tax has a positive but not significant effect on local revenue. Retribution for tourism objects has a positive but not significant effect on local revenue. The cost of acquiring land and building has a positive but not significant effect on local revenue.